Tidak ada perbedaan respon imun perokok berat dan perokok ringan karena asupan mikronutrien - Rahfiludin, Mohammad Zen; Ginandjar, Praba (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2013)
Background: Smoking may affect cytokine levels, including IFN-Î³, IL-6, and IL-10. Objectives: This study aimed to analyze the difference in levels of cytokines (IFN-Î³, IL-6 and IL-10) based on the degree of smoking, and how the daily intake of nutrient influence the relationship of smoking with cytokines level.Method: This was a cross sectional study. Study subject consisted of 23 adult, healthy, smoker men. Ethical clearance was issued by Commission of Ethics of Medical and Public Health Research, Faculty of Public Health Diponegoro University. Smoking variabel was obtained from questions. Level of cytokines examined consists of IFN-Î³, IL-6 and IL-10 was measured using ELISA (pg/dl). Nutritional intake was measured by method of 2x24-hour recall. The difference of level of IFN-Î³, IL-6, IL-10 and daily nutrient intake based on smoking degree was analyzed with Mann Whitney (Î± 0,05). Result: The result showed no difference in level of IFN-Î³, IL-6 and IL-10 found between group of light and heavy smokers. In the group of heavy smokers, daily nutrient intake was higher compare to light smokers. However, the significant difference only found in vitamin C (p = 0.042). Conclusion: Immune response, as measured by level of interferon gamma, interleukin 6 and interleukin 10, do not differ betwen light and heavy smokers due to micronutrient intakeÂ Keywords: heavy smoker, light smoker, interferon gamma, interleukin 6, interleukin 10